Reinterpreting ‘Khalifah Fil Ard’ as an Islamic Environmental Ethic for Addressing the 21st-Century Climate Crisis - Silva, Pedro; Souza, Felipe; Lima, Rafaela; Ummah, Andrian Khoirul (Journal of Humanities Research Sustainability, 2025)
Background. The accelerating climate crisis has prompted renewed global interest in ethical frameworks capable of guiding sustainable human–environment relations. In Islamic thought, the Qur’anic concept of khal?fah f?l-ar? (vicegerency on Earth) has traditionally been interpreted as a moral mandate for stewardship, accountability, and balanced interaction with the natural world. Purpose. This study aims to reexamine khal?fah f?l-ar? through an interdisciplinary lens that integrates Qur’anic exegesis, environmental philosophy, and climate ethics. Method. A qualitative research design is employed using textual hermeneutics, thematic content analysis of classical and modern tafsir, and comparative ethical analysis with environmental stewardship models. Results. The findings demonstrate that khal?fah f?l-ar? embodies a tripartite ethical structure: spiritual responsibility to God, moral responsibility to creation, and intergenerational responsibility for ecological continuity. These dimensions provide a normative foundation that contrasts sharply with anthropocentric paradigms driving ecological degradation. The research further shows that classical Islamic sources contain implicit ecological principles—such as moderation (wasatiyyah), balance (m?z?n), prohibition of harm (l? ?arar), and communal trust (am?nah)—which can form an integrated ethical framework for climate action. Conclusion. The study concludes that reinterpretation of khal?fah f?l-ar? offers a theologically grounded, ethically robust, and culturally resonant model for addressing climate crisis in Muslim-majority societies and globally. This work highlights the potential of Islamic environmental ethics to contribute meaningfully to sustainable policy, ecological education, and faith-informed climate activism.